The Effect of Isokinetic Testing Speed on the Reliability of Muscle Fatigue Indicators During a Hip Abductor-Adductor Fatigue Protocol - Gautrey, C. N.; Watson, T.; Mitchell, A. (International Journal of Sports Medicine, 2013)
The aim of this study was to investigate the reliability of fatigue indicators calculated from peak torque and total work during isokinetic speeds of 60, 90, 120 and 180° · s−1 during a hip fatigue protocol. 10 males suffering from a history of unilateral functional ankle instability and 10 male healthy controls performed 5 maximal concentric contractions on an isokinetic dynamometer. Following a 4 min rest period subjects were instructed to perform repeated maximal concentric contractions to fatigue, which was defined as 3 consecutive repetitions below 50% of the maximum peak torque value. Each testing speed was randomised with 24 h between speeds. The subjects were asked to return to the laboratory 7 days later to repeat the 4 speeds, with 24 h between speeds. Muscle fatigue was determined for each testing speed by the fatigue index, the percent decrease in performance and the slope of the regression equation. The most reliable fatigue determination method was the slope of the regression equation, when testing at a speed of 120° · s−1. It is recommended that future investigators examine and plot their data before choosing the slope of the regression equation as their fatigue indicator, as a linear model is required.
Keywords: intraclass correlation coefficient; standard error of measurement; functional ankle instability; fatigue index; percent decrease in performance; slope of the regression equation